Citizen or Subordinate: Permutations of Belonging in the United States and the Dominican Republic. (September 2013) - Aber, Shaina; Small, Mary
The Dominican Republic and the United States have both experienced tensions arising from migratory flows from poorer, less stable neighbors. Until recently, both countries had constitutions which conferred citizenship by birth with very limited exceptions. Despite these similarities, their respective discourses around jus soli citizenship, particularly for the children of unauthorized migrants from the poorer neighboring countries, have manifested in different ways. The identity of the United States as a nation of immigrants has limited the success of campaigns to revoke jus soli citizenship for the children of unauthorized immigrants, but the persistent articulation of this idea as a response to illegal migration has shifted the parameters of the immigration debate. In the Dominican Republic, the historical construction of national identity and anti-Haitian discourse has led to an evolution in Dominican law which codifies already established practices that deny citizenship to children of Haitian migrants. In both cases, movements that support more inclusive understandings of societal belonging, like the DREAMers in the United States and youth movements in the Dominican Republic, may offer the most effective way of protecting universal jus soli citizenship regimes.